The effect of personalized vitamin and mineral nutrition over skin microcirculation in athletes during the training period - Martusevich, A.; Minenko, I.; Nazarov, V.; Bocharin, I.; Kolokoltsev, M.; Romanova, E.; Vorozheikin, A.; Vrachinskaya, T.; Goranova-Spasova, R. (Journal of Physical Education and Sport, 2023)
It is relevant to study the influence of metabolism nutritional correction over systemic and local hemodynamics of the body in professional athletes. Purpose: to study the skin blood microcirculation dynamics in professional athletes who received a personalized vitamin and mineral complex. Materials and methods. 74 professional cyclic sports athletes took part in the research. They received a personalized vitamin and mineral complex daily during the training period for 30 days. Before the research start, the parameters of oxidative blood metabolism were studied in all athletes to individualize the appointment of metabolic correction agents. To do this, the level of parameters was compared with the untrained people's level characteristic. The state of blood microcirculation in the middle of the forearm was assessed using laser Doppler flowmetry on the LAKK-02 device (NPO Lazma, Moscow), before the start of the vitamin and mineral complex application course and immediately after its completion. Results. The research made it possible to establish the positive effect of personalized metabolic correction over the blood microcirculation functioning parameters. They manifested themselves in the form of blood flow velocity activation through small-diameter vessels (according to the level of microcirculation index), which was provided mainly due to endothelial (release of nitrogen monoxide by endotheliocytes), neurogenic and cardiac (contribution of pulse wave) regulation factors. Taking a vitamin and mineral complex contributed to a decrease in the bypass rate to physiological values.